Empathy and Burnout Among Physicians Providing Reanimatological and Surgical Treatment - Dalia Antinienė; Žydrūnė Kaklauskaitė (Lithuanian Sports University, 2018)
Background. Among scientifc publications it is observed that in medicine the aspect of interpersonal connection is underestimated while providing medical help (Steinhausen et al., 2014), and not enough attention is being allocated to the eﬀect of a physician's empathy in the treatment process (Hojat et al., 2002a). The lack of scientifc publications shows that this topic is under-researched and relevant. Thus, the purpose of the study was to determine relationships between empathy and burnout among practicing physicians. Methods. A total of 185 practicing physicians who provide reanimatological and surgical treatment participated in the research. A questionnaire was designed for the study, consisting of the Jeﬀerson Scale of Physician Empathy (Hojat, 2016), Copenhagen Burnout Inventory (Kristensen Borritz, Villadsen, & Christensen, 2005). Results. Research revealed that the expressiveness of empathy between doctors is not related to sex, age, work experience and speciality (p > .05). Also, it was found that younger physicians experienced more work-related burnout (p = .04). the study showed that there was no statistically signifcant relationship between empathy and burnout among physicians (p > .05). Conclusions. Research showed that physician's empathy was not related to demographic factors. Findings revealed that younger doctors experienced more work-related burnout than the older ones. Finally, connection between empathy and burnout was not found. Keywords: empathy, personal burnout, work-related burnout, patient-related burnout, physician